TINDAK PIDANA TAWURAN OLEH KELOMPOK REMAJA TERHADAP PETUGAS KEPOLISIAN DALAM UPAYA PENGAMANAN UNJUK RASA - Dessi Nindi Khadijah (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACTThe life of association, debate, and issue of debate has been obtained in Article 28 of the 1945 Constitution. In the discussion, the demonstration continued the group of adolescents who participated in becoming a mass. The demonstration moved arrogance to injure and make damage which caused it to visit each other. Based on these matters, the formulation of the problem that arises is related to the legal process of the adolescent group acts against police officers in an effort to secure demonstrations and the extent to which legal protection for children's rights commits criminal acts of a brawl in accordance with the Law on the Law on Violence Acts child. The method of research conducted in this study uses normative legal methods, namely by conducting library analysis. Brawl Crime against police officers in an effort to secure demonstrations. The legal process for children is always diverted from the level of the police, the prosecutor's office to the court is also carried out together with BAPAS, LPKS and related and verifiable institutions that can assist the court for the verdict, and the child will be placed in the LPKA (Child Development Foundation). Legal protection for children is guided by children's rights contained in the Juvenile Justice System Act.Keywords: Crime of Brawl, Child Suspect